Development and validation of a functional capacity test for collegiate dancers - Seifert, A. M.; Mullin, E. M.; Zehnder, S.; Paolone, V. J. (Journal of Dance Medicine & Science, 2021)
The purpose of this study was to design and validate a peak functional capacity test that is physiologically comprehensive and appropriate in movement for dancers with broad dance backgrounds. The Seifert Assessment of Functional Capacity for Dancers (SAFD) employs commonly utilized dance movements in progressively intense 3-minute stages, continued until volitional exhaustion. A convenience sample of 13 female collegiate dancers completed a familiarization trial of the SAFD, an SAFD trial, a peak treadmill test, and a second SAFD trial. Time to exhaustion, peak oxygen consumption (V02peak), respiratory exchange ratio (RER), heart rate (HR), blood lactate (BLa), and rate of perceived exertion (RPE) were measured with each trial. Intraclass correlation coefficients (ICCs) were used to assess test-retest reliability, while concurrent validity was analyzed using Pearson product-moment correlations (PPMCs). Strong ICCs were found between the SAFD trials for time to exhaustion, VO2peak, HR, and RPE, providing evidence of test-retest reliability of the SAFD. Significant positive relationships were found between time to exhaustion, VO2peak, HR BLa, and RPE for the SAFD and the treadmill test, providing evidence of concurrent validity of the SAFD. The data reported in the study provide initial evidence of reliability and validity for the SAFD.